Accounting comparability and relative performance evaluation by capital markets - Wu, Sang; Xue, Wenjie (Journal of Accounting and Economics, 2023)
This paper examines how accounting comparability affects the monitoring role and the risk allocation role of capital markets. We develop the statistical and informational properties of accounting reports under varying degrees of comparability. A perfectly comparable accounting information system enables investors to perfectly infer the difference between any two firms' future cash flows although investors remain uncertain about either firm's cash flow. Comparability alleviates entrepreneurs' moral hazard problem by strengthening the price response to the relative accounting performance, but can induce excessive price risk as well as residual systematic cash flow risk. Unlike the investors (users) who earn their surplus by bearing the residual systematic risk, the entrepreneurs (preparers) do not find perfect comparability desirable. Hence, a standard setter would mandate higher comparability than preferred by preparers, but not perfect comparability.